BS EN IEC 60840 AMD1. Power cables with extruded insulation and their accessories for rated voltages above 30 kV (Um= 36 kV) up to 150 kV (Um = 170 kV). Test methods and requirements. (27th August 2021) - British Standards Institution
No abstract available